Books and prints at the heart of the Catholic reformation in the Low Countries (16th-17th centuries) - Adam, Renaud; Marco, Rosa de; Walsby, Malcolm 1976- (Brill, 2023)
Often considered the advent of mass media, the use of books and prints by Protestants has been widely studied and has generated a rich and plentiful bibliography. In contrast, the production and use of the same media by the proponents of the Counter-Reformation have not received the attention they deserve, especially in the context of the Low Countries. The twelve chapters in this volume provide new perspectives on the efficacy of the handpress book industry to support the Catholic strategy in the Spanish Low Countries and underline the mutually beneficial relationship between the Counter-Reformation and the typographic world. This volume represents an important contribution to our understanding of the sociocultural and socioeconomic background of the Catholic Netherlands.
Keywords: Geschichte 1550-1650; Buchdruck; Gegenreformation; Niederlande; Catholics; Catholic Church; Christian literature, English; Konferenzschrift -- 23.02.2017-24.02.2017 -- Lüttich